Pelatihan Digital Marketing Dengan Optimalisasi Seller Center Pada Marketplace Shopee Untuk UMKM Kampung Jahe Merah Kecamatan Rungkut Kota Surabaya - Nugroho, Novianto Eko; Bambang Mahargiono, Pontjo; Ikhsan Budi Riharjo; Djawoto (LPPM Akademi Manajemen Administrasi Yogyakarta, 2025)
This community service initiative aims to improve digital marketing skills for MSMEs in Kampung Jahe, Kedung Baruk, Surabaya. MSMEs have an important role in the local economy, but many do not understand digital marketing strategies, especially in using the Shopee platform to increase sales. This activity aims to provide practical training and assistance through optimizing seller centers on the Shopee platform, so as to increase online transactions, sales, and competitiveness of MSMEs. The implementation method includes workshops and practical training sessions starting from identifying the needs of MSMEs, counseling, demonstrating the use of the platform, direct assistance, to evaluation and monitoring to measure the effectiveness of the program. Initial assessments showed a significant knowledge gap on digital marketing among participants. Through this training, participants are expected to understand and apply digital marketing techniques effectively to increase product sales. The program is also committed to ongoing support to help MSMEs adapt to evolving digital marketing trends. With a systematic and comprehensive approach, this initiative is expected to empower MSMEs in Kampung Jahe Merah to be more competitive, develop sustainably, and have a positive impact on the welfare of the local community.